Тестаменти як складова фамільних архівів. (Zaporizhzhia Historical Review, 2021)
The author analyzes informative potential of testaments as a historical source. The conclusion is made that the testaments are reliable material for characterising periods and ages, because many of them contain notices of Monarchial Charters or Hetman Universals or describe the way of obtaining estates and characterize their geographical locations.